The Influence of Shooting and Weight Training toward Handball Shooting Skills (Journal of Physical Education and Sports, 2020)
Weak throwing power will cause a lower throw rate so that it would be easy to be anticipated by an opponent's goalkeeper. Therefore, weight and shooting training is essential for handball athletes. This research aims to find out differences in weight and shooting training toward shooting skills and the interaction of shooting and weight training toward handball athletes' shooting skills. This research applied a 2x2 factorial design. The population consisted of 50 handball athletes in Pati municipality while the samples were taken by purposive sampling. The dependent variables were weight training using rubber and medicine balls and shooting practice with bounding takeoff compared to shooting training without bounding takeoff. The dependent variable was handball shooting. The applied data analysis was two-variant analysis (ANOVA) with significant level Î±=0,05.Shooting training with leap-with jump and medicine ball-weight training obtained an average score of 45.95 with a standard deviation of deviation 2.724. Shooting training with leap-without jumping and medicine ball-weight training obtained an average score 44.30 with a standard of deviation 3.262; shooting training without leap-with jump and rubber ball training obtained an average score 42.55 with a standard of deviation 2.762; shooting training with a leap-without jump and rubber ball-weight training obtained an average score 36.65 with a standard of deviation 2.834. There was an interaction between shooting training method and weight training toward shooting skill result with a Sig score = 0.002 < 0.05. The conclusion proves there was an influence between weight training with a medicine ball. It was effective than using a rubber ball to improve shooting skills. The shooting training method without leap-with jump was better than the shooting method with a leap-without jump. There was an interaction of the shooting method without leap-with jump and medicine ball-weight training. It was effective in improving handball shooting.